ENTRE FILÓLOGOS COMNENOS Y COPISTAS PALEÓLOGOS: OPIANO Y EURÍPIDES EN EL SALMANTICENSIS 31 (CON UNA CARTA AL PATRIARCA DE CONSTANTINOPLA) - Martínez Manzano, Teresa (Exemplaria Classica, 2016)
Salmanticensis 31, which contains works by Oppian and Euripides, is examined in this paper from the palaeographic, the tex- tual and the historic-cultural standpoints. Special attention is paid to its stemmatic connection to Laur. Plut. 31, 3, as well as to its exegetic apparatus (probably related with John Tzetzes ? work) and to John Ca- liandres (a copist belonging to the rst half of the 14th century). An unpublished letter to the Patriarch of Constantinople is tran- scribed as an appendix.